Environmental Sustainability and Land Ownership Rights: International Legal Perspectives - Haspada, Deny (Global Writing Academica Researching & Publishing, 2024)
Environmental sustainability and land ownership rights are critical issues in international law, addressing the balance between conservation and property rights. This study explores these complexities through a comparative legal analysis and literature review. The research aims to understand how international legal frameworks manage the interface between environmental protection and land ownership rights across diverse jurisdictions. Findings underscore the challenges and opportunities in achieving harmonious coexistence between these interests, emphasizing the pivotal role of international law in shaping policies that foster sustainable development while safeguarding property rights.